Design of a Compact Solar Cell Meshed Antenna for WLAN/WIMAX Application - Baccouch, C.; Bahar, C.; Sakli, H.; Aguili, T. (Advanced Electromagnetics, 2021)
Patch antenna is a low-profile antenna that has a number of advantages, low cost, light weight, easy to feed and their attractive radiation characteristics. For aWiMAX communication system, a microstrip patch antenna which operates at 2.76 GHz frequency band was presented in this work. The hybrid system solar cell antenna allows energy recovery as well as RF Transmission. A simulation process, withMATLAB, is used to determine the electrical power collected by the studied system as a photovoltaic cell. As a antenna, parameters such as gain, directivity, radiation pattern and radiated power were studied. Simulation results, showed a resonance frequency of the antenna at 2.76 GHz with an effective return loss of -18.64dB and a gain of 6.58dBi. Thereafter, an optical rectenna based on a solar cell antenna was proposed and studied.